2021
DOI: 10.1177/20420986211062965
|View full text |Cite
|
Sign up to set email alerts
|

Do women with venous thromboembolism bleed more than men during anticoagulation? Data from the real-life, prospective START-Register

Abstract: Background: Venous thromboembolism (VTE) is a frequent and serious disease that requires immediate and long-term anticoagulant treatment, which is inevitably associated with a risk of bleeding complications. Some studies, though not all, reported a higher risk of bleeding in female patients treated with either old anticoagulants [vitamin k antagonists (VKAs)] or recent anticoagulants [direct oral anticoagulants (DOACs)]. Furthermore, analyses of clinical trials reported an abnormal vaginal bleeding in women of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The combinations of nervous system disorders respectively paralysis and paresis , central nervous system haemorrhages and cerebrovascular accidents as well as speech and language abnormalities in combination with dabigatran were more frequently reported for males compared to females in both datasets. So far, literature is inconsistent with some studies reporting a higher prevalence of bleedings with DOACs in males while others observed higher risks of bleeding events for females or did not observe any sex differences regarding bleeding events at all 42–44 . Sex‐specific differences in the expression of enzymes affecting the metabolism and pharmacodynamics of dabigatran could contribute to these findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The combinations of nervous system disorders respectively paralysis and paresis , central nervous system haemorrhages and cerebrovascular accidents as well as speech and language abnormalities in combination with dabigatran were more frequently reported for males compared to females in both datasets. So far, literature is inconsistent with some studies reporting a higher prevalence of bleedings with DOACs in males while others observed higher risks of bleeding events for females or did not observe any sex differences regarding bleeding events at all 42–44 . Sex‐specific differences in the expression of enzymes affecting the metabolism and pharmacodynamics of dabigatran could contribute to these findings.…”
Section: Discussionmentioning
confidence: 95%
“…So far, literature is inconsistent with some studies reporting a higher prevalence of bleedings with DOACs in males while others observed higher risks of bleeding events for females or did not observe any sex differences regarding bleeding events at all. [42][43][44] Sex-specific differences in the expression of enzymes affecting the metabolism and pharmacodynamics of dabigatran could contribute to these findings. Thus, further research on the underlying polymorphisms could investigate sex-specific genetic risk constellations requiring a dose adjustment of dabigatran.…”
Section: Adr-drug Combinations More Frequently Reported For Females O...mentioning
confidence: 99%
“…The design of the START registry has been previously described. 7 Briefly, the START (Clinicaltrial.gov NCT02219984 ) is an observational, prospective, multicentre, dynamic cohort study of adults (≥18 years) starting anticoagulation therapy, whatever the indication for treatment and drug/dosage. Data are captured using an electronic case report form (eCRF) designed by Softime 90 Snc (Bologna Italy) and submitted electronically via a secure Web site to the registry-coordinating center at the “Arianna Anticoagulazione” Foundation (Bologna, Italy), which is the owner of the registry and is responsible for checking the completeness and accuracy of data collected from medical records.…”
Section: Methodsmentioning
confidence: 99%
“…As for information on index events, their nature was classified as (a) unprovoked, when not temporally associated with any potential triggering conditions or RFs; (b) associated with weak RF, such as minor, arthroscopic or laparoscopic general surgery, pregnancy or puerperium, contraceptive or replacement hormonal therapy, long trip, minor trauma, stay in hospital, reduced mobility (not complete immobilization); (c) provoked by transient major RF, as elsewhere detailed. 7 The site of events was classified as (a) DVT [either proximal or isolated distal], when thrombosis of deep veins was not associated with diagnosis of PE; or (b) cases with PE, when a PE event was associated with DVT, or was isolated. Splanchnic vein thrombosis (SVT) and cerebral vein thrombosis (CVT) were defined as unusual site vein thromboses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation